Statistics for Political Analysis: Understanding the Numbers - Marchant-Shapiro, Theresa (Sage CQ Press, 2014)
Keywords: Statistics; Textbooks; Textbooks; Political statistics; dept.psc; faculty_collection

American Republicanism and the fin-de-siècle imperialism debate - O’Hara, Jonathan (Journal of Political Ideologies, 2014)
Aristotelian republicanism rests on an important premise, that persuasion is more virtuous than coercion. Nonetheless, there is an uneasy tension between the two approaches to rule in the republican tradition. This is particularly true with respect to Aristotle’s views on foreign policy, wherein coercive means of bringing about justice among nations may be viewed as much an offspring of republican thought as the exercise of moral suasion to the same end. This article takes this interesting tension in Aristotelian republican thought and attempts to apply it as an exegetical lens for looking into the republican ideological contours of the fin-de-siècle American imperialism debate. Particular attention is paid to how the tension in republican approaches to rule informed and helped give shape to the debate. Analysed through this lens is the rhetoric of two of the debate’s most important exponents, Theodore Roosevelt, advocating greater coercive means, and Carl Schurz, an advocate of moral suasion. © 2014 Taylor & Francis.
Keywords: dept.psc; foreign policy; imperialism; morality; political ideology; social justice